Characterization of barium titanate: BaTiO3 (BT) ceramics prepared from sol-gel derived BT powders - Deshpande, S. B.; Godbole, P. D.; Khollam, Y. B.; Potdar, H. S. (Journal of Electroceramics, 2005)
Sol-gel synthesis was attempted at room temperature by adding drop wise a clear solution (made by reacting BaCO3 with glacial acetic acid) to an equi-molar solution of titanium tetrabutoxide in isopropanol (IPA) and acetic acid. The gelation occurred within 30 minutes. The as-dried gel was calcined at 750 degrees C/6 h in air to obtain carbon free BaTiO3 powders. The resulting BT powders were further pressed into pellets and sintered at 1280 degrees C/4 h in air to get dense ceramics (density similar to 94%). XRD and SEM techniques were used for phase and microstructure analysis respectively. The room temperature relative permittivity (e) of 1280 increased to 7200 (at Curie temperature of 127 degrees C) at 1 kHz frequency. The dissipation factor (tan delta) similar to 1.6% was observed in these samples. Also, the ferroelectric properties such as spontaneous polarization (Ps similar to 13 mu C/cm(2)), coercive field (E-c similar to 4.0 kV/cm) and dielectric strength (similar to 34 kV/cm) are estimated for these samples. These performance parameters are compared with the available standard data from the literature.
Keywords: barium titanate; ferroelectricity; Microstructure; relative permittivity; sol-gel processing